Time Performance Analysis Using Earned Value on the Construction of the Aranaway Kiram Bridge in Banjar Baru City - Tezar Aulia, Rachman (INTI International University, 2024)
When implementing a project in the field, it is fairly uncommon for numerous projects to be delayed or even halted. This also has an impact on project cost escalation, resulting in project losses. Earned value analysis can help manage construction projects efficiently and effectively. The results value analysis was done to estimate the extent to which the project was carried out according to the work plan. This assessment was performed on the Aranaway Kiram Bridge Construction project in Banjarbaru City. The project was aimed to determine weekly time performance and project completion time. The method employed was earned value analysis. According to the results of the analysis method (earned value analysis), the results from the 3rd to the 18th week experienced delays, as evidenced by the performance of the Schedule Variance (SV) which was Negative (-) and the Schedule Performance Index (SPI) which was less than 1, but work accelerated in the 19th week of the Banjarbaru City Aranaway Kiram Bridge Construction Project, as evidenced by the SV performance which was Positive (+) and SPI greater than 1. The research results estimated the project's completion time as 253 days.